1998
DOI: 10.1084/jem.187.9.1543
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination with DNA Encoding an Immunodominant Myelin Basic Protein Peptide Targeted to Fc of Immunoglobulin G Suppresses Experimental Autoimmune Encephalomyelitis

Abstract: We explore here if vaccination with DNA encoding an autoantigenic peptide can suppress autoimmune disease. For this purpose we used experimental autoimmune encephalomyelitis (EAE), which is an autoaggressive disease in the central nervous system and an animal model for multiple sclerosis. Lewis rats were vaccinated with DNA encoding an encephalitogenic T cell epitope, guinea pig myelin basic protein peptide 68–85 (MBP68–85), before induction of EAE with MBP68–85 in complete Freund's adjuvant. Compared to vacci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
50
0
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(52 citation statements)
references
References 25 publications
1
50
0
1
Order By: Relevance
“…Annealing temperatures were 55°C for Fc␥RI and GAPDH, 60°C for Fc␥RIIa and Fc␥RIIb, and 62°C for Fc␥RIII. The PCR reaction was stopped after 20,23,26,29,32,35,38,41, and 44 cycles at the very end of the extension phase (72°C), and 5-l samples were obtained.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Annealing temperatures were 55°C for Fc␥RI and GAPDH, 60°C for Fc␥RIIa and Fc␥RIIb, and 62°C for Fc␥RIII. The PCR reaction was stopped after 20,23,26,29,32,35,38,41, and 44 cycles at the very end of the extension phase (72°C), and 5-l samples were obtained.…”
Section: Methodsmentioning
confidence: 99%
“…The function of Fc␥RIIIb, which lacks an intracellular domain, is still unknown (18). Coordinate expression of Fc␥R has been implicated in various diseases involving ICs, such as diabetes (19), systemic lupus erythematosus (20,21), multiple sclerosis (22,23), autoimmune anemia (24,25), and RA (26).…”
mentioning
confidence: 99%
“…Indeed, initial reports have demonstrated that induction of experimental autoimmune encephalomyelitis can be prevented by immunizing rodents with pDNAs encoding a variable ␤-chain segment of an encephalogenic TCR (28) or with epitopes derived from autoantigens used to induce the disease process (29,30). However, the efficacy of pDNA immunization to suppress established autoimmunity was not examined in these studies.…”
mentioning
confidence: 88%
“…Of importance is that spontaneous GAD65-specific Th1 cell reactivity is first detected in 4-wk-old NOD mice and reaches maximal levels in animals 12 wk of age (5,6). Two recent experimental autoimmune encephalomyelitis studies have demonstrated that T cells are tolerized via anergy/deletion mechanisms, and autoimmunity is prevented by immunizing rodents with pDNAs encoding peptides derived from the autoantigens used to induce disease (29,30). In these studies, however, the animals lacked primed autoantigen-specific T cells at the time of pDNA immunization.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, gentle and quiet immune reactions could be obtained by DNA vaccine administration. In our and other's laboratories, immune therapies with DNA vaccines have been examined in autoimmune disease models (14)(15)(16)(17) and have been found to be effective in preventing the diseases without the use of adjuvants. Here, we developed nonviral A␤ DNA vaccines and were able to reduce the amyloid burden in the cerebral cortex and hippocampus of Alzheimer's disease model (APP23) mice by vaccination.…”
mentioning
confidence: 99%